Assessment of GIS-interpolation techniques for groundwater evaluation : a case study of the Sandveld, Western Cape, South Africa - Munch, Zahn (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004